Click to Chat

1800-2000-838

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```        solve:-
(2x-7)(x-3)(x+3)(2x+5)=91```
8 years ago

147 Points
```										Dear sayan
(2x-7)(x-3)(x+3)(2x+5)=91
(2x-6-1)(x-3)(x+3)(2x+6-1)=91
[2(x-3)2 - (x-3)][ 2(x+3)2 - (x+3)]=91
4(x-3)2(x+3)2  -2(x+3)2(x-3)-2(x-3)2(x+3) +(x-3)(x+3) = 91
4(x-3)2(x+3)2  -2(x+3)(x-3)2x +(x2-9) = 91
[x+2(x-3)(x+3)]2  =100
or 2x2 +x-18 =±10
+ sign
2x2 +x-28 =0
- sign
2x2 +x-8 =0
now solve these two equation and find solution
Please feel free to post as many doubts on our discussion forum as you can. If you find any question Difficult to understand - post it here and we will get you the

```
8 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »
• Complete JEE Main/Advanced Course and Test Series
• OFFERED PRICE: Rs. 15,900
• View Details